2022
DOI: 10.1371/journal.pone.0275664
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of white matter pathology, hypoperfusion, lesion load, and stroke recurrence to language deficits following acute subcortical left hemisphere stroke

Abstract: Aphasia, the loss of language ability following damage to the brain, is among the most disabling and common consequences of stroke. Subcortical stroke, occurring in the basal ganglia, thalamus, and/or deep white matter can result in aphasia, often characterized by word fluency, motor speech output, or sentence generation impairments. The link between greater lesion volume and acute aphasia is well documented, but the independent contributions of lesion location, cortical hypoperfusion, prior stroke, and white … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(123 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, other studies did not find a consistent association between cortical hypoperfusion and aphasia after acute subcortical LH stroke. 42,43 In this study, we identified the caudate nucleus as the only subcortical structure whose amount of damage (independent of total lesion size) was associated with apraxia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, other studies did not find a consistent association between cortical hypoperfusion and aphasia after acute subcortical LH stroke. 42,43 In this study, we identified the caudate nucleus as the only subcortical structure whose amount of damage (independent of total lesion size) was associated with apraxia.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, other studies did not find a consistent association between cortical hypoperfusion and aphasia after acute subcortical LH stroke. 42,43…”
Section: Discussionmentioning
confidence: 99%
“…EC tracts are also adjacent to portions of SLF ( Schmahmann et al, 2009 ), raising the possibility that these two pathways are commonly damaged together in stroke affecting the middle cerebral artery. It is also possible that the EC contributes to language via subcortical connections that support language either directly or through domain-general processes ( Kuljic-Obradovic, 2003 , Sharif et al, 2022 ). The MOG, on the other hand, may be related to visual identification of items and objects near the ‘beginning’ of the ventral language stream ( Fridriksson et al, 2016 , Hickok and Poeppel, 2004 , Hickok and Poeppel, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study showed that cortical hypoperfusion in the left hemisphere was more likely a determining factor of language deficits in subcortical aphasia rather than direct effect of the lesion in the basal ganglia ( n = 19) ( Celebi et al, 2022 ), replicating an effect observed earlier in acute subcortical aphasia ( Hillis et al, 2002 ). However, another study did not find cortical hypoperfusion to be a contributing factor to the severity of acute subcortical aphasia ( Sharif et al, 2022 ). The discrepancies in the results are likely due to varying methods used to assess cortical perfusion, with the latter study with null effects relying on hyperintense vessels on FLAIR scans to estimate regions of decreased blood flow.…”
Section: Neurovascular Changes In Strokementioning
confidence: 99%